Research on the system error performance of coherent orthogonal frequency division multiplexing system with M-distribution in satellite-to-ground laser communication - Yi WANG; Yaping WANG (Tongxin xuebao)
In order to alleviate the influence of atmospheric turbulence on the performance of satellite-to-ground laser communication system,based on the M-distribution atmospheric channel model,a multi-carrier coherent orthogonal frequency division multiplexing (OFDM) modulation system was proposed for uplink and downlink in the satellite-to-ground laser communication.The closed-form expression of bit error rate (BER) of coherent OFDM modulation system was derived.The relationship between the zenith angle,receiving aperture,signal-to-noise ratio (SNR),optimal beam divergence angle,and optimal transmission radius and the BER were studied under weak,and strong atmosphere turbulence,and compared with binary coherent differential phase shift keying (DPSK) modulation.Both the theory and the simulation results show that compared with coherent DPSK modulation,the bit error performance of the coherent OFDM modulation system in the satellite-to-ground laser communication system is better.